Analysis of The Practicality of Google Sites-Based Teaching Materials to Improve Student Learning Outcomes - Hikmawati, Hikmawati; Suastra, I Wayan; Suma, Ketut; Sudiatmika, A A Istri Agung Rai; Susanti, Dian (Jurnal Ilmiah Profesi Pendidikan, 2024)
The aim of this research is to conduct an analysis of the practicality of Google Sites-based teaching materials to improve student learning outcomes. Testing the practicality of teaching materials is one of the stages of the teaching material development model that uses the 4D model. The research was conducted at SMP Negeri 8 Mataram in the 2022/2023 academic year. Data on the practicality of teaching materials was obtained by administering user response questionnaires, namely teachers (10 people) and students (34 people). The score weights use a Likert scale with four answer options, namely Strongly Agree (score 4), Agree (score 3), Disagree (score 2), or Strongly Disagree (score 1). The practicality criteria are divided into four criteria, namely: Very impractical (percentage 0-25); Not practical (percentage 26-50); Practical (Percentage 51-75); Very practical (Percentage 76-100). The research results show that the average teacher assessment of Google Sites-based teaching materials for improving student learning outcomes is 93.4 which is in the category: "Very Practical". Aspects of teacher assessment of teaching materials are reviewed from four aspects, namely: Content, Language, Presentation, Graphics. The average student assessment of Google Sites-based teaching materials to improve student learning outcomes is 95.5 which is in the category: "Very Practical". Aspects of student assessment of teaching materials are viewed from four aspects, namely: Perception of Convenience, Usefulness, Attractiveness, Actual Use of the Product.